Kata Ganti Orang dalam Bahasa Pagu (Isam) - Mutji, Elsye Jesti (Universitas Sam Ratulangi, 2015)
Pagu (Isam) language is a member of the NorthHalmaheran family of the West Papuan phylum. Pagu (Isam) Language isÂ the language is almost extinctbecauseitsspeakers are less. Because of that problem the author hopes this research willbe motivate the other writersto preserve local languages in a study.This research is a description about personal pronounin Pagu (Isam) language. Personal pronounrefers to a specific person or thing and changes its form to indicate person, number, gender, and function.The problems of this research are what are the form and function used in the sentence of Pagu (Isam)language.The result of this research will be concluded not only descriptionaboutpersonal pronoun in Pagu (Isam) language but also one aspect of personal pronounthatnot yet known there are third personal pronoun with neutral gender andthenat possessive pronoun we just need to addâ€œtoâ€as a marker that it is possessive pronoun.Key word: Description, Personal Pronoun, Pagu (Isam) Language